Mental health in elite athletes: Increased awareness requires an early intervention framework to respond to athlete needs - Purcell, R.; Gwyther, K.; Rice, S. M. (Sports Medicine, 2019)
The current `state of play` in supporting elite athlete mental health and wellbeing has centred mostly on building mental health literacy or awareness of the signs of mental ill-health amongst athletes. Such awareness is necessary, but not sufficient to address the varied mental health needs of elite athletes. We call for a new model of intervention and outline the backbone of a comprehensive mental health framework to promote athlete mental health and wellbeing, and respond to the needs of athletes who are at-risk of developing, or already experiencing mental health symptoms or disorders. Early detection of, and intervention for, mental health symptoms is essential in the elite sporting context. Such approaches help build cultures that acknowledge that an athlete`s mental health needs are as important as their physical health needs, and that both are likely to contribute to optimising the athlete`s overall wellbeing in conjunction with performance excellence. The proposed framework aims at (i) helping athletes develop a range of self-management skills that they can utilise to manage psychological distress, (ii) equipping key stakeholders in the elite sporting environment (such as coaches, sports medicine and high-performance support staff) to better recognise and respond to concerns regarding an athlete`s mental health and (iii) highlighting the need for specialist multi-disciplinary teams or skilled mental health professionals to manage athletes with severe or complex mental disorders. Combined, these components ensure that elite athletes receive the intervention and support that they need at the right time, in the right place, with the right person.